The effect of choice options in training curricula on the demand for and supply of apprentices - Jansen, Anika [Verfasser]; De Grip, Andries [Verfasser]; Kriechel, Ben [Verfasser] (My University, 2017)
"Building on Lazear's skill weights approach, we study the effect of having more or less heterogeneity in the training curriculum on the demand for and supply of apprentices. Modernizations of training curricula provide us with a quasi-experimental setting as these modernizations can be seen as a relatively exogenous shock. We argue that firms will train more apprentices when they have more choice options in the training curriculum because of (1) the higher productivity of graduates who have acquired more skills that are relevant for the firm, and (2) firms' higher market power in the wage bargaining process with graduates. We test this hypothesis on data on the demand for apprentices in Germany in all occupations from 2004 to 2014. We find that a more heterogeneous curriculum increases both firms' demand for and the supply of apprentices." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 2.2.2.1 Ausbildungsordnungen; G 1.3.1.1 Ausbildungsstellenmarkt; Betriebliche Berufsausbildung; Ausbildungsordnung; Berufsstruktur; Monoberuf; Spezialisierung; Wahlqualifikation; Zusatzqualifikation; Einflussfaktor; Ausbildungsplatzangebot; Ausbildungsplatznachfrage